1993
DOI: 10.1016/0014-5793(93)80485-d
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric characterization of the stable complex of myosin subfragment 1 with ADP and beryllium fluoride

Abstract: The thermal unfolding of the myosin subfragment 1 (Sl) in its stable complex with ADP and beryllium fluoride (Sl . ADP . BeF;) was studied by differential scanning calorimetry. It has been shown that the structure of the Sl molecule in the Sl ADP . BeF; complex is similar to that of Sl in its complex with ADP and orthovanadate (Sl ADP . Vi) but differs radically from that of nucleotide-free Sl and Sl in the Sl . ADP complex. It is concluded that the Sl . ADP . BeF; complex can be considered, like the Sl . ADP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 14 publications
5
20
0
Order By: Relevance
“…Thus, the effects of the SH1 modification on the conformational changes of $1 induced by the formation of the S1.ADP.Vi complex depend on the sulfhydryl reagent employed; NEM is the most effective, especially in comparison with 1,5-IAEDANS or IAA. The formation of the stable S1.ADP.BeFx complex causes an effect similar to that observed for the S1.ADP.Vi complex although slightly less pronounced (Bobkov et al, 1993) (Fig. 2B).…”
Section: Effects Of Modification Of Sh1 Group Of Cys-707supporting
confidence: 55%
See 2 more Smart Citations
“…Thus, the effects of the SH1 modification on the conformational changes of $1 induced by the formation of the S1.ADP.Vi complex depend on the sulfhydryl reagent employed; NEM is the most effective, especially in comparison with 1,5-IAEDANS or IAA. The formation of the stable S1.ADP.BeFx complex causes an effect similar to that observed for the S1.ADP.Vi complex although slightly less pronounced (Bobkov et al, 1993) (Fig. 2B).…”
Section: Effects Of Modification Of Sh1 Group Of Cys-707supporting
confidence: 55%
“…We showed that formation of the S1.ADP-Vi complex causes a global change of $1 conformation which is reflected in pronounced increase of $1 thermal stability, in considerable increase in cooperativity of the thermal transition, and in significant change of $1 domain structure (Levitsky et al, 1992). Similar but slightly less pronounced effect was found for the formation of the S1.ADP-BeF~ complex (Bobkov et al, 1993). Thus, the studies of the $1 thermal denaturation by DSC allow to probe the conformational changes of the whole $1 molecule caused by formation of the S1.ADP.Vi and S1-ADP.BeFx complexes.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…In the presence of ADP these analogues also bind to S1 and induce a significant increase of the S1 thermal stability [8,12]. However, interaction of S 1 with F-actin leads to rapid release of BeFx or A1F4" fzom active site of the S1 ATPase [15].…”
Section: Resultsmentioning
confidence: 99%
“…S 1 was obtained by digestion of myosin filaments t~om rabbit skeletal muscles by chymotrypsin [1t]: Concentration of S1 was determined spectrophotometrically by using E TM = 7.5 at 280 urn. The ternary complexes S1-ADP-BeFx and S1-ADP-A1F4" were obtained by the methods described earlier [8,12].…”
Section: Methodsmentioning
confidence: 99%